2020
DOI: 10.1080/13617672.2020.1736969
|View full text |Cite
|
Sign up to set email alerts
|

Religious literacy: a way forward for religious education?

Abstract: In this paper the central findings of a research project into religious literacy are presented. This project sought to answer the question as to whether or not religious literacy can be a way forward for religious education (RE). Starting with the idea of 'literacy', dominant approaches religious literacy in the literature are examined. An educational argument is developed, building on a definition of literacy in relation as being an effective navigation of a domain. At this point a question is raised about wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 26 publications
0
16
0
1
Order By: Relevance
“…By 'literacy' we refer to the ability to do something with that knowledge. Regarding the context of RE, we appreciate the influence of other literacies and epistemic frameworks in developing our account of epistemic literacy; including religious literacy (Hannam et al, 2020), religion and worldviews literacy (Shaw, 2020), epistemic switching (Gottlieb & Wineburg, 2012) and epistemic insight (Billingsley et al, 2013). Recent theoretical formulations of religious literacy stress the rejection of imperialist understandings of literacy in which the powerful (in a) community decide what is the dominant language (Hannam et al 2020).…”
Section: What Do We Mean By 'Epistemic Literacy'?mentioning
confidence: 99%
See 2 more Smart Citations
“…By 'literacy' we refer to the ability to do something with that knowledge. Regarding the context of RE, we appreciate the influence of other literacies and epistemic frameworks in developing our account of epistemic literacy; including religious literacy (Hannam et al, 2020), religion and worldviews literacy (Shaw, 2020), epistemic switching (Gottlieb & Wineburg, 2012) and epistemic insight (Billingsley et al, 2013). Recent theoretical formulations of religious literacy stress the rejection of imperialist understandings of literacy in which the powerful (in a) community decide what is the dominant language (Hannam et al 2020).…”
Section: What Do We Mean By 'Epistemic Literacy'?mentioning
confidence: 99%
“…Regarding the context of RE, we appreciate the influence of other literacies and epistemic frameworks in developing our account of epistemic literacy; including religious literacy (Hannam et al, 2020), religion and worldviews literacy (Shaw, 2020), epistemic switching (Gottlieb & Wineburg, 2012) and epistemic insight (Billingsley et al, 2013). Recent theoretical formulations of religious literacy stress the rejection of imperialist understandings of literacy in which the powerful (in a) community decide what is the dominant language (Hannam et al 2020). Religion and worldviews literacy, meanwhile, calls for one's reflexivity combined with the appropriate disposition and tact that results from (1) knowledge of the actual religious/non-religious landscape, and (2) an understanding of the category of religion/worldview (Shaw, 2020).…”
Section: What Do We Mean By 'Epistemic Literacy'?mentioning
confidence: 99%
See 1 more Smart Citation
“…From this, we developed a conception of cultural intelligence (distinct from religious literacy) which we believe learning outside the classroom is particularly suited to develop. Whereas religious literacy is often related to essential knowledge that enables easy communication of core concepts (Hirsch 1987)to enable them to navigate the religious world (Hannam et al 2020), the concept of cultural intelligence was oriented to situating this religious knowledge within the wider competences for intercultural encounter in lived experience.…”
Section: The Second Cyclementioning
confidence: 99%
“…Religious literacy, in the form of knowledge about religion(s), is simply not enough. In addition, as Hannam, et al, (2020) point out, these competencies and abilities may instead be found in other school subjects, such as history, geography, literature, social sciences, domestic science, and psychology. From my perspective, the term "religious literacy" is by no means necessary in order to be able to establish and elaborate on the purpose of RE, even though the religious literacy discourse admittedly articulates a few themes and aspects that are worth exploring further in an educational context, such as the generic abilities (i.e., qualification) to discern, analyze, and explore.…”
mentioning
confidence: 99%